Hearing Outcome of Low-tone Compared to High-tone Sudden Sensorineural Hearing Loss - Psillas, George; Rizou, Aikaterini; Rachovitsas, Dimitrios; Tsiropoulos, Gabriel; Constantinidis, Jiannis (International Archives of Otorhinolaryngology, 2019)
Introduction Low-tone sudden sensorineural hearing loss (SSHL) is a well-recognized disease, in which the hearing loss is restricted to low frequencies. In contrast to low-tone SSHL, high-tone SSHL is characterized by high-frequency (4,000, 8,000 Hz) hearing loss and preservation of low-, middle-frequency hearing.Objective The objective of this study is to compare the hearing recovery and long-term outcome of low-tone SSHL with those of patients affected by high-tone SSHL in a follow-up of ∼ 3 years.Methods The low-tone SSHL and high-tone SSHL groups included 27 and 20 patients, respectively; the patients of both groups were treated with intravenous steroids. Predictive factors (gender, affected side, delay of treatment, follow-up time) were also examined.Results Overall, complete hearing recovery was observed in 77.7% of the patients in the low-tone SSHL group and in 15% of the patients in the high-tone SSHL group. In the high-tone SSHL group, a higher proportion of patients reported tinnitus compared with the low-tone SSHL group (13 cases [65%] versus 3 cases [11%]); however, recurrences were more common in the low-tone SSHL (22%, 6 patients) compared with the high-tone SSHL (2 cases [10%]) group. No predictive factor was found to statistically impact on hearing outcome.Conclusion After initial therapy, the low-tone SSHL patients have more favorable hearing outcome than high-tone SSHL patients. However, recurrences occurred more frequently in the low-tone SSHL group, while the high-tone SSHL group was more often accompanied by residual symptoms, such as tinnitus.
Keywords: sudden hearing loss; low tone; prognosis